Mathematics | Sum of squares of even and odd natural numbers

We know sum squares of first n natural numbers is \frac{n(n+1)(2n+1)}{6}.

How to compute sum of squares of first n even natural numbers?
We need to compute 22 + 42 + 62 + …. + (2n)2

EvenSum = 22 + 42 + 62 + .... + (2n)2 
        = 4 x (12 + 22 + 32 + .... + (n)2)
        = 4n(n+1)(2n+1)/6
        = 2n(n+1)(2n+1)/3

Example:

Sum of squares of first 3 even numbers =
                 2n(n+1)(2n+1)/3
               = 2*3(3+1)(2*3+1)/3
               = 56
22 + 42 + 62 = 4 + 16 + 36 = 56



How to compute sum of squares of first n odd natural numbers?
We need to compute 12 + 32 + 52 + …. + (2n-1)2

OddSum  = (Sum of Squares of all 2n numbers) - 
          (Sum of squares of first n even numbers)
        = 2n*(2n+1)*(2*2n + 1)/6 - 2n(n+1)(2n+1)/3
        = 2n(2n+1)/6 [4n+1 - 2(n+1)] 
        = n(2n+1)/3 * (2n-1)
        = n(2n+1)(2n-1)/3

Example:

Sum of squares of first 3 odd numbers = n(2n+1)(2n-1)/3
                                      = 3(2*3+1)(2*3-1)/3
                                      = 35
12 + 32 + 52 = 1 + 9 + 25 = 35

Please write comments if you find anything incorrect, or you want to share more information about the topic discussed above

Don’t stop now and take your learning to the next level. Learn all the important concepts of Data Structures and Algorithms with the help of the most trusted course: DSA Self Paced. Become industry ready at a student-friendly price.

My Personal Notes arrow_drop_up

Improved By : VaibhavRai3

Article Tags :

Be the First to upvote.


Please write to us at contribute@geeksforgeeks.org to report any issue with the above content.